Decarbonizing Development : Smoothing the Transition and Protecting the Poor - World Bank (Washington, DC, 2015)
Stabilizing climate change entails bringing net emissions of carbon dioxide (CO2) to zero. CO2 stays in the atmosphere for hundreds, if not thousands, of years. As long as one emit more than captured or offset through carbon sinks (such as forests), concentrations of CO2 in the atmosphere will keep rising, and the climate will keep warming. Countries can follow three principles in their efforts to create a zero-carbon future: (a) planning ahead for a future with zero emissions, (b) getting carbon prices and policies right, and (c) smoothing the transition and protecting the poor. In this context, the report presents managing the political economy of reform without getting captured by vested interests; and ensuring poor people benefit from the reform.